Weight change and incident metabolic syndrome in Iranian men and women; a 3 year follow-up study - Sarbakhsh Parvin; Hadaegh Farzad; Zabetian Azadeh; Azizi Fereidoun (BMC Public Health, 2009)
Abstract Background Although the association of weight gain and developing metabolic syndrome (MetS) has been reported in the Western and Asian populations, data on the gender-stratified effects of weight change (including weight loss) on incident MetS and its components in the Middle East Caucasians is still scarce. Methods A total of 1431 men and 2036 women aged ≥ 20 years with BMI > 18.5 kg/m2 were followed over 3 years. Multivariate logistic regression analysis was used to estimate the relative risk (RR) of MetS and its components (the Adult Treatment Panel III definition) associated with gender-stratified quintiles of percent weight change. Subjects with MetS at baseline were excluded for analyzing the RR of MetS. Results There was 20.4% (95% CI, 19.6–21.2) age-adjusted incident MetS (18.4% male vs. 23.1% women). In men, mild weight gain (WG) predicted high waist circumference (WC) and high triglyceride; moderate WG predicted MetS (RR 2.5, 95% CI 1.4–4.3), high WC and high blood pressure (BP); large WG predicted MetS (RR 3.2, 95% CI 1.8–5.7) and its components, except for high fasting plasma glucose. In women, mild WG predicted MetS (RR 2.5, 95% CI 1.4–4.3), high WC and high BP; moderate WG predicted Mets (RR 4.6, 95% CI 2.7–8.0), high WC and high triglyceride; large WG predicted MetS (RR 6.6, 95% CI 3.8–11.3) and its components except for low HDL-cholesterol. Mild weight loss had protective effect on high WC in both genders and MetS in men (RR 0.5, 95% CI 0.26–0.97, P = 0.04). Conclusion Weight change showed different effects on MetS in men and women. In women, mild WG predicted MetS; however, mild weight loss was protective against MetS in men and high WC in both genders.